DEVELOPING THEORIES OF TEACHING ACADEMIC INDONESIAN TO NON–LANGUAGE MAJORS: WAYS OF COLLECTING AND ANALYZING DATA - A. Chaedar Alwasilah (Indonesian JELT, 2005)
Writing is the skill most neglected in language education in Indonesia.  High school graduates in general are not ready to write academic Indonesian, let alone academic English. This paper discusses practices of teaching Indonesian at pre-college and college levels, theories and practice of writing, and language versus non-language specialists as writing instructors. The objectives of this paper are to demonstrate that: (1) different techniques of data collection generate different types of data, (2) the more data you have, the better you triangulate the findings, and (3) the quality of data is not only determined by its collecting techniques, but also by its relevance with research objectives. In this paper, I want to share the methodology of several studies on teaching writing at college levels I have conducted in the last eight years in English and non-English departments in Indonesia. The studies have revealed the following: (1) language education has failed to provide pre-college students with fundamentals of academic writing, (2) freshman Indonesian should be focused on developing academic or technical writing, (3) the success of teaching academic writing at college levels is dependent on the success of teaching writing at pre-college levels, (4) non-Indonesian language lecturers have the potential to be empowered to teach academic writing in non-language departments, (5) ethnic literature-based writing has the potential to revitalize the ethnic literature, and (6) collaborative writing including peer reviewing and teacher-student conferencing has been effective for coping with big classes of writing. Keywords:  College Indonesian, collaborative writing, qualitative research